Multi-method evidence on investors’ reactions to managers’ self-inclusive language - Chen, Zhenhua; Loftus, Serena (Accounting, Organizations and Society, 2019)
We investigate the joint effect of managers’ self-inclusive language (SIL) and performance news on investors’ reactions to accounting disclosures. We identify two types of SIL: individual SIL, which includes first-person singular pronouns (e.g., I, me) and collective SIL, which includes first-person plural pronouns (e.g., we, us). When performance news is negative, individual SIL implies that a manager is claiming sole responsibility for the unfavorable event whereas collective SIL and SEL diffuse responsibility. Therefore, we predict higher perceptions of manager credibility for individual SIL relative to collective SIL or self-exclusive language (SEL) when performance news is negative, which, in turn, increase investment judgments. We use a between-subjects experiment to test our predictions. Results show higher perceptions of manager credibility and higher investment judgments for individual SIL relative to collective SIL or SEL when performance news is negative. Results of a maximum likelihood estimation suggest that perceptions of manager credibility mediate the effect of individual SIL on investment judgments, supporting the notion that individual SIL exerts an indirect effect on investment judgments. We supplement experimental evidence with an analysis of managers’ SIL in a large sample of earnings conference calls. We document a positive (negative) market reaction to individual (collective) SIL when performance news is negative, consistent with our Hypothesis. We also find a positive market reaction to individual SIL when news is positive. Overall, our study offers multi-method evidence of the impact of a subtle and easily overlooked component of managers’ language on investors’ judgments.